In Vitro Evaluation of MgB2 Powders as Novel Tools to Fight Fungal Biodeterioration of Heritage Buildings and Objects - Gheorghe, Irina; Avram, Ionela; Maria Corbu, Viorica; Măruţescu, Luminita; Popa, Marcela; Balotescu, Irina; Blăjan, Ion; Mateescu, Venus; Zaharia, Daniela; Dumbravă, Andreea Ştefania; Zetu, Octavia Emilia; Pecete, Ionut; et al. (Frontiers in Materials, 2021)
The 17th–19th century wooden and stone churches are an iconic symbol for the Romanian national heritage, raising urgent needs for the development of efficient and ecofriendly restoration and preservation solutions. Nanotechnology has a great but largely unexplored potential in this field, providing new tools and methods to achieve higher consolidation and protection efficiency, mainly due to the ability of nanoparticles to inhibit the growth and metabolic activity of different biodeteriorating agents, including fungi. The purpose of the present study was to report for the first time on the efficiency of MgB2 materials, mainly prized for their practical superconducting properties, against a large collection of filamentous fungal strains recently isolated from biodeteriorated wooden and stone heritage objects. Four types of MgB2 powders, with a crystallite size of 42–113 nm, were tested by qualitative (on 149 strains) and quantitative (on 87 strains) assays. The cytotoxicity was evaluated by the microscopic analysis of SiHa cells morphology and Hep2 cell cycle analysis and the ecotoxicity by the Allium test. The tested filamentous fungal strains belonged to 11 different genera, and those isolated from mural paintings and wooden objects exhibited the best capacity to colonize the inert substratum. All MgB2 powders exhibited similar and relatively low minimal inhibitory concentrations (MIC) values against the Aspergillus and Penicillium isolates, which were predominated among isolates. From the tested powders, PVZ and CERAC proved to be more efficient against the strains isolated from stone and wood materials, while LTS was active against the fungal strains colonizing the mural paintings and museum objects. The cytotoxicity results indicated that the tested powders are toxic for the human cells at concentrations higher than 50 µg/ml, but, however, the very short lifetime of these NPs prevents their accumulation in the natural environment and, thus, the occurrence of toxic effects. The tested powders proved to be ecofriendly at the active antifungal concentrations, as suggested by the phytotoxicity test results. Taken together, our results suggest the potential of the MgB2 materials for the development of environmentally safe antifungal substances, which can be used in the control of the material cultural heritage biodeterioration process.